Most Frequent Topography of Ruptured Aneurysms In Uruguay: Presentation of a multicentric prospective study of a series of 211 cases.: https://doi.org/10.59156/revista.v36i04.614 - Jaume , Alejandra; Romero, Mariana; Negrotto, Matias; Gil, Juan; Macadam, J. Pedro; Pereira, Lucia (Revista Argentina de Neurocirugía, 2023)
Background. Subarachnoid hemorrhage (SAH) is more common in females between the fourth and sixth decade of life6. 80 to 85% of SAH are due to ruptured aneurysm. Intracranial aneurysms can be classified in different ways according to their etiology, size, morphology or topography.Objectives. To describe the topographic and morpho-structural features of aneurysms in our country.Methods. All patients over 18 years old with a diagnosis of SAH, who consulted to a healthcare center in the country between 11/01/2019 and 10/31/2020, were included in the study. The clinical-epidemiological characteristics and comorbidities at the time of diagnosis, the type of treatment received and clinical evolution variables during the following 6 months were collected. The significance level of evidence used in the tests was 5%. Due to the multicenter and national nature of the study, it had to be subjected to an evaluation by all the Ethics Committees of the participating health institutions, and by the National Research Ethics Commission.Results. A total of 211 cases were observed in the evaluated period. The average age was 57 years with a predominance of the female sex (75%). In 82% of cases, the vascular study used was CT angiography. The most common aneurysmal topography was anterior communicating artery (27.5%), middle cerebral artery (27%), and posterior communicating artery (23%). 27% suffered multiple aneurysms. In 74% of cases, some type of specific treatment was indicated (43% open surgery and 31% endovascular therapy).Conclusions. This work provides the first figures on the topography of ruptured aneurysms in Uruguay, being this comparable to what is described in the international literature.
Keywords: aneurysm; subarachnoid hemorrhage; topography; treatment